1946
DOI: 10.1021/ja01216a025
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation and Identification of Alkylcyclopropanes: 1,1,2-Trimethylcyclopropane and 1,2-Dimethyl-3-ethylcyclopropane

Abstract: as that described was heated three-quarters of an hour and then poured into 200 ml. of water.Sodium bicarbonate was added to excess.After reaction ceased, the solution was extracted twice with chloroform and the combined, dried extracts were concentrated under reduced pressure to a residual oil which was dissolved without delay in about 70-100 ml. of water and assayed spectrophotometrically. Under the conditions described, 30% was a typical yield. Addition of a few crystals of hydroquinone is advisable. Soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1954
1954
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…We found that the bands observed by Allen and collaborators 27 about 3080cm-1 in the spectra .of nitrocyc1opropanes must necessarily be assigned to the 2v(N0 2 ).ss vibration 48 . In this connection we want to point out the results of the study carried out by Cole 33 who found a single band (about 3040cm -1) in the spectra of a series of natural compounds containing a three membered ring built in the molecule in a way evident from formula I. 1 II III v(CH) 3058, 3003 cm-1 v(CH) 3030, 2960 cm- 1 We measured the spectra of several compounds of this type (Table VI Nos [50][51][52][53][54] and observed that even in these compounds we may find two absorption bands of variable positions belonging to the mentioned stretching vibrations of the CH2 group. The band due to the symmetric vibration was shifted below the limit of 3000 em -1.…”
Section: Infrared Spectra Of Compounds Containing a Cyclopropane Ringmentioning
confidence: 94%
See 1 more Smart Citation
“…We found that the bands observed by Allen and collaborators 27 about 3080cm-1 in the spectra .of nitrocyc1opropanes must necessarily be assigned to the 2v(N0 2 ).ss vibration 48 . In this connection we want to point out the results of the study carried out by Cole 33 who found a single band (about 3040cm -1) in the spectra of a series of natural compounds containing a three membered ring built in the molecule in a way evident from formula I. 1 II III v(CH) 3058, 3003 cm-1 v(CH) 3030, 2960 cm- 1 We measured the spectra of several compounds of this type (Table VI Nos [50][51][52][53][54] and observed that even in these compounds we may find two absorption bands of variable positions belonging to the mentioned stretching vibrations of the CH2 group. The band due to the symmetric vibration was shifted below the limit of 3000 em -1.…”
Section: Infrared Spectra Of Compounds Containing a Cyclopropane Ringmentioning
confidence: 94%
“…The CH Bond Stretching Vibration Region of I-Phenyl-I-methylcyc1opropane(1) and Phenylcyclopropane(2) …”
mentioning
confidence: 99%
“…This reactor was jacketed and 1 Present address, F rankl Photogra phic Services, Washington, D. C. , Prescnt address, National Institn tes of Health , Bethesda, Md . 3 Figurcs in brackets indicate the literature refereuces a t the end of this paper.…”
Section: Reaction Vesselsmentioning
confidence: 99%
“…This cycloj)araffin was prepared by the reaction of zinc with 1,3-dibr0mobutane, according to the method of Bartleson, Burk, and Lankelma [3]. Several runs were made ; a typical preparation is described below.…”
Section: Methylcyclopropanementioning
confidence: 99%
See 1 more Smart Citation